Comparative analysis among blood pressure devices, from different brands, used in the pharmaceutical clinic service in a public pharmacy, Sinop-MT. - Bernardo, V. R.; Zampieron, R. G.; Sheng, L. Y.; Rissato, M. A. R.; Leitzke, R. C. Z. (Scientific Electronic Archives, 2020)
Systemic arterial hypertension is a disease that affects approximately 1.13 billion of the world population. This paper aims to analyze the values obtained through blood pressure measurements by three different types of devices, namely: aneroid, semiautomatic and automatic, in participants who demanded assistance in the extension project â€œConsultÃ³rio FarmacÃªuticoâ€ (Single Health System/SUS) in Sinop, MT, twice a week, with blood pressure measurements, following the guidelines of the Brazilian Society of Hypertension, and the manual of each device, which describe the techniques for measuring blood pressure in its particularities. The survey was carried out from February 2017 to April 2018. At the end of each measurement, the results were recorded and analyzed, being compared among each other. By the statistical analyzes carried out, it was possible to compare the blood pressure measurements obtained with an auscultatory method and two oscillometric methods, making it possible to verify and guide each patient who preferably uses only one device model in their measurements, since the variation of methods that the devices can present, can be harmful and confuse to the patient, because depending on the values found, they may worry the mentioned patient in carrying out his self-care.